Pengaruh Efektivitas Alat Permainan Puzzle Terhadap Perkembangan Motorik Halus Pada Anak Usia 4-5 Tahun Di Ypi Zaky River Valley Kabupaten Deli Serdang Tahun 2020 - Heny Rista; Juliana Munthe; Srilina Br Pinem; Lasria Simamora; Ade Srimulyani (Pro Health Jurnal Ilmiah Kesehatan, 2022)
Childhood is the most important period for children's development so it is called the Golden Age, usually at this time children aged 0-6 years who experience the fastest stages of physical and spiritual growth and development, both physically and mentally. This study aims to analyze the effect of the effectiveness of playing puzzles on fine motoric development in children aged 4-5 years in Zaky River Valley Kindergarten. Population is all elements research subjects of children who study at YPI Zaky River Valley as many as 20 students, the number of students from March to May 2020. This is an analytical survey with a cross sectional research design. Retrieval of data using a checklist sheet. The data were processed by univariate analysis using descriptive statistics and bivariate analysis using the Wilcoxon test. The results of the analysis for knowledge and attitudes with the Wilcoxon test showed that the value of p = 0.000 which means less than Î± = 0.005, then H0 is rejected and Ha is accepted. This means that there is an effect of the effectiveness of playing puzzles on the level of anxiety on fine motoric development in children aged 4-5 years at YPI Zaky River Valley Deli Serdang Regency in 2020.